Historical Legacies of the Pre-industrial Family Systems: Cohabitation - Torras, Inés Gil (Vilnius University Open Series, 2025)
This paper discusses a cultural explanation for the rise of cohabitation in the last decades in Europe. For doing so, I approach this phenomenon from the field of historical legacies of pre-industrial family systems. The literature regarding the history of marriage and cohabitation points that, before the institutionalization of marriage, different characteristics of family systems and family norms (such as co-residence of parents with their adult children, dowry, or inheritance) were relevant to explain why some regions in Europe had a higher use of cohabitation (called back then informal marriage). Regarding the current rise of this practice, the Second Demographic Transition theory (SDT) points to the ideational change toward individualism and anti-conformism as the main cause of the rise of cohabitation. And, not surprisingly, the literature about legacies of historical family systems recently connected preindustrial family features (such as the number of generations living in the same household) with the persistence of the values and attitudes that seem to be linked to the recent changes in family formation. These 3 bodies of literature highlight the potential of the field of historical legacies of the family to explain the current family behavior, such as cohabitation.